Nature and History in the Knowledge of Value: A study in Bernard Lonergan' s account of value. - Steenburg, David John Frederick (My University, 1994)
This dissertation examines Bernard Lonergan' s understanding of value, its assumptions and its development, for the sake of determining the role of human nature and human historicity in the experience of value. The categories of nature and history reflect a specifically modem form of the long-standing question of the relationship between physis and nomos- i.e., nature and convention, or 'nature and nurture'-for modernity has made us accutely aware of the historicity of cultural conventions. We ask of Lonergan: how or to what extent is the experience of value determined by human nature, and how or to what extent is it historically conditioned?
To understand Lonergan' s position one must appreciate both the difference and the continuity between his earlier and later thought. Lonergan' s earlier thought reflects a rather Kantian fonnalistic account of value as the rational good, but his later thought embraces Scheler' s non-fonnal, material account of value-i.e., the good is an object of natural appetite-a position in which affectivity plays a role in revealing value. In spite of this development, there yet remains an underlying unity: there is a fundamental opposition of affect and intellect that precludes the possibility of understanding value as both rationally and materially good. Lonergan associates affect with natural spontaneity, and intellect with the deliberate:, progressive dynamic of history. Because of this, in his earlier work he presents value as rationally, and therefore historically, determined; yet in his ma1ure position value is grasped primarily in affective apprehensions, which are ahistorical intuitions, grounded in human nature and the 'reasons of the heart'.
In response, it will be argued that this dichotomy of feeling and rationality can be transcended without sacrificing Lonergan' s account of self-transcendence.
Keywords: Bernard Lonergan; value; human nature; historically conditioned